Gratitude, Optimism, and Subjective Well-Being: Empowering Honorary Teacher to Thrive Amid Challenges - Masyhuri, Masyhuri; Sudirman, Subhan Ajrin; Fadhli, Muhammad; Qaderi, Sabza Gol (Universitas Muhammadiyah Yogyakarta, 2025)
Honorary teachers in special schools often face complex challenges, both professionally and emotionally, impacting their subjective well-being. This study aims to examine the influence of gratitude and optimism on subjective well-being honorary teachers teaching in special schools. This quantitative study uses an ex post facto approach with multiple linear regression tests. The samples size in the study was 152 honorary teachers teaching in special schools, selected using cluster random sampling techniques. The measuring instruments used were a modification of the Gratitude Scale (α = .789), a modification of the Optimism Scale (α = .889), and a combination of the Satisfaction with Life Scale (SWLS) and the HOT Scale to measure Subjective Well-Being (α = .802). Data analysis was carried out using SPSS) version 25. Hypothesis testing using multiple linear regression showed that gratitude and optimism simultaneously had a significant effect on subjective well-being (F = 793.986; sig. = .000; R = .702; R² = .492). Gratitude (t = 12.935; sig. = .000) and optimism (t = 63.816; sig. = .000) also had significant individual effects. The effective contribution of gratitude was 23.8%, and optimism was 25.4%. Thus, the results of this study indicate that gratitude and optimism together have a very significant effect on subjective well-being. Therefore, policymakers and educational institutions must strengthen these psychological aspects to improve honorary teachers' subjective well-being in special schools.